Sites for Gamma-ray Astronomy in Argentina - Rovero, Adrian Carlos (2008)
We have searched for possible sites in Argentina for the installation of large air Cherenkov telescope arrays and water Cherenkov systems. At present seven candidates are identified at altitudes from 2500 to 4500 m. The highest sites are located at the NW of the country, in La Puna. Sites at 2500 and 3100 m are located in the West at El Leoncito Observatory, with excellent infrastructure. A description of these candidate sites is presented with emphasis on infrastructure and climatology.